Biomarkers of Epithelial-Mesenchymal Transition in Squamous Cell Carcinoma - Scanlon, C.S. (SAGE Publications, 2012)
An understanding of the process by which tumor cells destroy the basement membrane of the surface epithelium, invade, and metastasize is essential to the development of novel treatment of head and neck squamous cell carcinoma (HNSCC). In recent years, there has been increased interest in the role of epithelial-mesenchymal transition (EMT) in invasion. EMT is a process that describes the development of motile, mesenchymal-like cells from non-motile parent epithelial cells. There are 3 known types of EMT that mediate development, wound healing, and carcinogenesis. This review summarizes studies of known EMT biomarkers in the context of HNSCC progression. The biomarkers discussed come from a wide range of proteins, including cell-surface proteins (E-cadherin, N-cadherin, and Integrins), cytoskeletal proteins (α-Smooth Muscle Actin, Vimentin, and β-catenin), extracellular matrix proteins (Collagens, Fibronectin, and Laminin), and transcription factors (SNAIL1, SNAIL2, TWIST, and LEF-1). Overall, the findings of these studies suggest that EMT mediates HNSCC progression. The mechanistic role of the EMT markers that have been associated with HNSCC should be more clearly defined if new anti-HNSCC therapies to block EMT progression are to be developed.